Diagnosis Sifat Kimia Tanah dan Serapan Hara Pada Tanaman Nenas yang dibudidayakan Pada Tanah Gambut di Desa Kualu Nenas: Diagnosis of Soil Chemical Properties and Nutrition about Planning Cultivation on Peat Soil in Kualu Nenas Village - Sri Mulyani; Siti Zahrah; Sulhaswardi (Jurnal Ecosolum, 2022)
Management of peat soil for pineapple cultivation in Kualu Pineapple Village is still very traditional. In planting not using spacing, fertilization only uses fertilizers containing N, namely urea. In addition, there are differences in principles in managing peat, namely that there are farmers who add ameliorant ingredients and some do not. The purpose of this study was to determine the chemical properties of the soil, and nutrient uptake of pineapple plants in Kualu Nenas Village where the soil was given dolomite lime ameliorant and without ameliorant. This research method uses qualitative (survey) and quantitative (laboratory analysis) methods. A sampling of plants whose soil was given dolomite lime ameliorant and soil without ameliorant was carried out by purposive sampling technique. The research data were analyzed by a T-test to determine the difference between the chemical properties and nutrient uptake of pineapple plants. The T-test was analyzed using the SAS program (SAS User Manual Version 9, 2004). The results of this study were that the soil PH, P-available, K-dd, Ca-dd, Mg-dd, CEC, and base saturation content in pineapple plantations where the soil was treated with dolomite lime ameliorant had a significantly higher value based on the T-test compared to pineapple plantations with no ameliorant. Nutrient uptake of N, P, K, Ca, and Mg in pineapple leaves was not significantly different between plants whose soil was treated with dolomite lime ameliorant and those without ameliorant.